2011
DOI: 10.1186/1471-2334-11-42
|View full text |Cite
|
Sign up to set email alerts
|

A first assessment of the genetic diversity of Mycobacterium tuberculosis complex in Cambodia

Abstract: BackgroundCambodia is among the 22 high-burden TB countries, and has one of the highest rates of TB in South-East Asia. This study aimed to describe the genetic diversity among clinical Mycobacterium tuberculosis complex (MTC) isolates collected in Cambodia and to relate these findings to genetic diversity data from neighboring countries.MethodsWe characterized by 24 VNTR loci genotyping and spoligotyping 105 Mycobacterium tuberculosis clinical isolates collected between 2007 and 2008 in the region of Phnom-Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…In the Mekong river delta in Viet Nam, overall a lower transmissibility [18]. Among adults, a genotype analysis of strains from Phnom Penh has shown that among non-multidrugresistant strains, Beijing genotypes accounted for 21% of the total [7] comparable to our 19% from roughly the same area.…”
Section: Discussionmentioning
confidence: 64%
“…In the Mekong river delta in Viet Nam, overall a lower transmissibility [18]. Among adults, a genotype analysis of strains from Phnom Penh has shown that among non-multidrugresistant strains, Beijing genotypes accounted for 21% of the total [7] comparable to our 19% from roughly the same area.…”
Section: Discussionmentioning
confidence: 64%
“…We confirm that the IO lineage predominates in the region, as it does in other Southeast Asian countries. For example, in Northern Vietnam, this lineage accounts for 41.7% of cases, and in Cambodia, 68% of cases [5,30,31]. Based on LSPs, only the Beijing, IO and EuA lineages were identified from pulmonary TB patients in Northeast Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…Large RDs contain genes that can affect the phenotype whereas small RDs interfere with gene expression around the indel site. Different lineages of Mtb were suggested to exhibit different degrees of virulence, of association with drug resistance and response to BCG vaccination [5]. These mycobacterial lineages associated with particular geographical regions and human ethnic groups suggest adaptation to regional human populations and host-pathogen co-evolution [1].…”
Section: Introductionmentioning
confidence: 99%
“…CAS and EAI genotypes, along with the Beijing genotypes, contribute to the major proportion of clinical strains in India (58). EAI strains have also been reported as one of the major genotypes in many countries of Southeast Asia and Africa (9). EAI strains have been shown previously to be associated with slow transmissibility in human populations/patients in some parts of the world (10) and along with CAS strains have been suggested to be involved in extrapulmonary tuberculosis in some regions of the world (11, 12).…”
Section: Genome Announcementmentioning
confidence: 99%